The alpha thalassaemias. - Higgs, D; Weatherall, D (2009)
Recent work in the alpha thalassaemia field has started to provide some indication of the mechanisms involved in the very high frequency of the different forms of alpha thalassaemia among the populations of tropical countries, and, at the same time, is starting to define at least some of the mechanisms for its remarkable phenotypic heterogeneity. These diseases continue to provide extremely valuable models for the better understanding of the regulation of the alpha globin genes, and for human molecular pathology in general. The much less common disorders, ATR-16 and ATR-X are also providing valuable information about the spectrum of molecular lesions associated with different forms of mental retardation and about the molecular mechanisms involved in their varying phenotypes.